Case Report: Hereditary transthyretin (ATTRv) amyloidosis: The p.G103R mutation of the transthyretin gene in a Han Chinese family is associated with vitreous hemorrhage - Shen, Junhui; Yu, Hao; Lin, Jijian; Zhang, Li; Pan, Xiaohong; Chen, Zhiqing (Frontiers in Genetics, 2022)
Hereditary transthyretin (ATTRv) amyloidosis is a rare disease caused by transthyretin gene (TTR) mutation. We identified that the p.G103R mutation of the TTR gene in a Han Chinese family was associated with vitreous hemorrhage. The proband was a 48-year-old woman who had progressive visual impairment in both eyes for 12 years. A Glass wool–like posterior vitreous cortex attached to the posterior retinal surface of both eyes was found using ocular coherence tomography. Visual acuity improved after the first vitrectomy. Two years later, the patient underwent two more vitrectomies because of vitreous opacity recrudescence. Four years later, she presented with vitreous hemorrhage in the right eye. The vitreous fluids acquired during the vitrectomy showed increased vascular endothelial growth factor, basic fibroblast growth factor, interleukin-6, interleukin-10, vascular cell adhesion molecule, and interleukin-8. Mutation sequencing revealed a heterozygous mutation in nucleotide c.307G > C (p.G103R) in exon 3 of the TTR gene in the proband (IV-13), her daughter (IV-9), and her fourth sister (III-11). To our knowledge, this is the first case of ATTRv amyloidosis caused by a p.G103R mutation of the TTR gene associated with vitreous hemorrhage in China.